Effects of Educational Methodology on Ludic and Verbal Development in preschool Children in Mexico and Ecuador during the context of the Pandemic - María Caridad Torres Guzmán; Luis Quintanar Rojas; Yulia Solovieva (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
Preschool education plays a fundamental role in the child's further development and performance in pri-mary school. Although the traditional teaching model predominates in basic education, various pedagogical models have been proposed as an alternative to the traditional model (Dipp etal., 2008; Aljabreen, 2020). The present study contrasts the effects of two educatio-nal methodologies applied online during the COVID-19 Pandemic, in Mexico and Ecuador, on the develop-ment of preschool children. 14 first grade children from 3 to 4 years old participated (6 from Mexico and 8 from Ecuador). The two methodologies were applied for 6 months, and two evaluations were carried out, initial and final, through the 'Developmental Assessment for Younger Preschool Children' (Solovieva & Quintanar, 2014). The results show that the two educational met-hodologies contribute in a similar way on the develop-ment of language, the acquisition of object actions and respect for social norms. In the same way, differential contributions from each educational methodology are recorded. The educational methodology used in Mexico favored the development of voluntary activity, while the educational methodology applied in Ecuador favored the development of symbolic activity.